PRARANCANGAN NASKAH PENDADARAN PABRIK GREEN EPICHLOROHYDRIN Kapasitas DENGAN BAHAN BAKU GLISEROL DARI PRODUK SAMPING PABRIK BIODIESEL 75.000 Ton/Tahun - , LATIFA SENIORITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Preliminary design of Green Epichlorohydrin Plant from glycerin with production capacity of 75,000 ton/year is intended to fulfill epichlorohydrin demands, especially for Asia Pacific markets. Global demands of epichlorohydrin in 2017 is estimated to be increased as much as 405 kilotons than 2012âs demands.. This plant is planned to be built in Dumai, Riau, which has total area of 27.9 Ha and will be operated in 330 days a year with employ over 224 persons. The production of epichlorohydrin is carried out by two main processes